Selection of the Best Swimming Athletes using MCDM-AHP and VIKOR Methods - Akmaludin, Akmaludin; Sidik , Sidik; Iriadi, Nandang; Arfian, Andi; Surianto, Adhi Dharma (Politeknik Ganesha Medan, 2021)
The process of selecting the best swimming athletes is carried out in several test stages, the first is the ability in the four basic swimming styles which often contested in international competitions and the second test is the basic physical abilities possessed by a number of swimming athletes. The tests related to the swimming style consist of breaststroke swimming, butterfly swimming, backstroke swimming and crawlstroke swimming, while the plyometrics test consists of banded knee jump, squat jump, jump to side, and dept jump, Due to the large number of selections, a test is required for every athlete. The purpose of this selection is to find the best swimming athletes who will be competed in the international swimming class event. The nine athletes of millenium aquatic swimming club that were selected previously, they are the forerunners of the selected swimming athletes and will be evaluated on a representative basis, which is the best among the nine athletes. The method used in the evaluation and selection process uses two continuous methods, namely the AHP and VIKOR methods. From the results selection assessment, it was found that the best three of the nine nominations selected, the first position selected was AT2 with an index 0.00, the second position was AT8 with an index 0.25 and the third position was AT7 with an index 0.61. Thus it can be concluded that the AHP and VIKOR methods can be used as decision support to determine optimally in the optimal selection process for swimming athletes.